2012
DOI: 10.1109/lawp.2012.2224311
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth Enhancement of a Printed Slot Antenna With a Pair of Parasitic Patches

Abstract: A printed microstrip-line-fed slot antenna with a pair of parasitic patches for bandwidth enhancement is proposed in this paper. By using the parasitic patches along the microstrip feed line, an additional resonance is excited and a good performance of bandwidth enhancement can be obtained. The proposed antenna is designed and manufactured successfully. The measurement shows a good agreement with the simulation. From the measured results, the enhanced impedance bandwidth, defined by voltage standing wave ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 7 publications
0
40
0
Order By: Relevance
“…Various modification approaches of monopole antennas have been adopted for bandwidth enhancement. Some of these include incorporation of a dielectric resonator, ring slot, inverted T in ground plane, simple bevel design, element smoothening, utilizing shorting pins, designing fractal elements, inserting wide open slots, integrating parasitic elements, using various substrate thicknesses, and truncated ground plane …”
Section: Introductionmentioning
confidence: 99%
“…Various modification approaches of monopole antennas have been adopted for bandwidth enhancement. Some of these include incorporation of a dielectric resonator, ring slot, inverted T in ground plane, simple bevel design, element smoothening, utilizing shorting pins, designing fractal elements, inserting wide open slots, integrating parasitic elements, using various substrate thicknesses, and truncated ground plane …”
Section: Introductionmentioning
confidence: 99%
“…It is found that wide-slot antenna contributes to large bandwidth [10,12] whereas narrow-band slot antenna provides very small bandwidth [1]. Parasitic patches have been used along the feed line to further enhance the impedance bandwidth of the rotated square slot antenna in [14]. The narrow bandwidth of a cavity backed slot antenna has been improved by inserting a via-hole above the I-shaped slot [15].…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent decades, performance improvement of microstrip antennas play a great attention among the research community and multiple techniques have been proposed to enhance the performance parameters such as gain , bandwidth , efficiency , and directivity of microstrip antennas with a compact size. Gain of the antenna can be improved by using frequency selective surface (FSS) reflector , hybrid substrates , negative permeability meta material , etc.…”
Section: Introductionmentioning
confidence: 99%